Participation by the NGOs in housing for the urban poor in Bangladesh - Rahman, Mohammed Mahbubur (BRAC University, 2010)
Many non-government organisations (NGOs) are involved in various development programs in Bangladesh, targeting the urban poor, who also lack proper housing. Yet they have not been widely involved in urban housing. This paper is based on the author’s 1998 Robert McNamara Fellowship study titled 'Role of the NGOs in Urban Housing for the Poor in Bangladesh’ of the World Bank’s Economic Development Institute. It discusses the obstacles and limitations of involvement by the NGOs in housing for the urban poor in Bangladesh.